Proceedings of the 3rd International Conference on Material, Mechanical and Manufacturing Engineering 2015
DOI: 10.2991/ic3me-15.2015.323
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Blade Tip Foil Thickening on Tip Vortexes in Ducted Propeller

Abstract: A thick tip foil blade was designed to reduce the tip leakage flow and weaken the tip vortexes in ducted propeller 19A/Ka4-55. The thick tip foil was constructed by normal extrusion of the original tip foil. The maximum thickness of the foil increased from 1.64% chord length to 7.64%. The commercial CFD code CFX was employed to simulate the flow field of the two ducted propellers. From the performance curves, it could be concluded that the tip foil thickening will not affect the thrust and torque of the ducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Furthermore, there is enough distance between the leading edge roughness and the re-entrant jets (Ds), and therefore, the local pressure distribution on a leading edge is greatly affected by the leading edge roughness. 70 As the shape of the blade tips can have a significant effect on tip leakage, foils with various tip shapes, such as squealer tips, [128][129][130] thickened tips, 131 rounded tips, 132,133 and C-grooves 134 have been studied. The casing grooves may also serve as an effective solution for suppressing the tip-leakage vortex (TLV), according to Kang et al 135 and Hah et al 136 It has been confirmed, however, that the effect of passive control strategies in the control of tip leakage is greatly influenced by gap size.…”
Section: B Blade Profile and Geometry Modificationmentioning
confidence: 99%
“…Furthermore, there is enough distance between the leading edge roughness and the re-entrant jets (Ds), and therefore, the local pressure distribution on a leading edge is greatly affected by the leading edge roughness. 70 As the shape of the blade tips can have a significant effect on tip leakage, foils with various tip shapes, such as squealer tips, [128][129][130] thickened tips, 131 rounded tips, 132,133 and C-grooves 134 have been studied. The casing grooves may also serve as an effective solution for suppressing the tip-leakage vortex (TLV), according to Kang et al 135 and Hah et al 136 It has been confirmed, however, that the effect of passive control strategies in the control of tip leakage is greatly influenced by gap size.…”
Section: B Blade Profile and Geometry Modificationmentioning
confidence: 99%
“…Tip thickening is another method for improving the flow pattern near the tip clearance. Mei and Zhou [80] studied the effect of tip thickening in a ducted propeller. Their numerical results show that a thick-tip foil remarkably reduces the strength of TLV, and the pressure drop in the TLV core on the middle chord section is reduced by approximately 33% from that of the original propeller.…”
Section: Tip Shapementioning
confidence: 99%
“…Their results show that the proposed C-groove successfully suppresses the primary TLV in its inception stage by groove-jet impingement and weakens the secondary TLV by the groove-channel flow, which is illustrated in Tip thickening is another method for improving the flow pattern near the tip clearance. Mei and Zhou [80] studied the effect of tip thickening in a ducted propeller. Their numerical results show that a thick-tip foil remarkably reduces the strength of TLV, and the pressure drop in the TLV core on the middle chord section is reduced by approximately 33% from that of the original propeller.…”
Section: Tip Shapementioning
confidence: 99%
See 1 more Smart Citation